Analysis of Factors Affecting Economic Growth in Mataram City - Oni Apriani; Muaidy Yasin; Masrun , Masrun (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
This study aims to analyze the factors that influence the economic growth of Mataram City by looking at the effect of the labor force participation rate and gross fixed capital formation of Mataram City on economic growth. This study uses secondary data that is time series from BPS publications for the 2007-2019 period. The method used in this study is the OLS (ordinary least square) method using the Eviews 12 program. The results showed that the independent variables in this study explained the variable economic growth rate of Mataram City by 20.24 percent, while for 79.76 percent which was influenced by other factors outside this study. Partially, the labor force participation rate variable does not have a significant effect on Mataram City, which means that the variable cannot provide positive economic growth, while the gross fixed capital formation variable also has no significant and positive effect on economic growth. Simultaneously, the labor force participation rate variable and the gross fixed capital formation variable of Mataram City together have no effect and are insignificant to the economic growth of Mataram City.